Methane Gas Production from a Landfill Model under Saturated Conditions - Sapari, Nasiman (Universiti Putra Malaysia Press, 1995)
A laboratory experiment was conducted to examine methane gas production from landfills under saturated moisture conditions. A landfill model was constructed from a 4-m PVC cylinder of 20 em internal diameter, to simulate municipal landfill cells of 2.5 m thickness on sandy soils. The same soil was used as the cover material. The landfill was operated over a period of 30 months, for the first 24 months without leachate mobilization and the last 6 months with leachate mobilization. A total of 1.40 pore volume of leachate from the solid waste layer was mobilized into the underlying sand and pebble layers during the last 6 months. Gas production from the landfill during the first 24 months was 22 ml/day/kg wet weight of solid waste. It contained 55% methane. The rate of production increased, to an average of 77 ml/day/kg wet weight of solid waste, during leachate mobilization operation at a flow rate of 1.6 cm/day. Methane fermentation took place in the underlying sand layer but not in the middle of the solid waste layer because the pH in the solid waste layer was too low (5.3) associated with a very high COD of about 30,000 mg/I.